2021
DOI: 10.3389/fmicb.2021.746410
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus velezensis AP183 Inhibits Staphylococcus aureus Biofilm Formation and Proliferation in Murine and Bovine Disease Models

Abstract: The increasing frequency of S. aureus antimicrobial resistance has spurred interest in identifying alternative therapeutants. We investigated the S. aureus-inhibitory capacity of B. velezensis strains in mouse and bovine models. Among multiple B. velezensis strains that inhibited S. aureus growth in vitro, B. velezensis AP183 provided the most potent inhibition of S. aureus proliferation and bioluminescence in a mouse cutaneous wound (P = 0.02). Histology revealed abundant Gram-positive cocci in control wounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Many beneficial bacteria are found on the human skin surface, which coexist with the body, expel exogenous or endogenous pathogens, and maintain the integrity of the skin barrier [66][67][68]. B. belesii can inhibit the formation and proliferation of S. aureus biofilms in vivo and in vitro [69]. Rhodococcus has been proven to have good biodegradability and can degrade a large number of organic compounds, including some toxic and persistent substances [70].…”
Section: Composition and Abundance Of Skin Microbiotamentioning
confidence: 99%
“…Many beneficial bacteria are found on the human skin surface, which coexist with the body, expel exogenous or endogenous pathogens, and maintain the integrity of the skin barrier [66][67][68]. B. belesii can inhibit the formation and proliferation of S. aureus biofilms in vivo and in vitro [69]. Rhodococcus has been proven to have good biodegradability and can degrade a large number of organic compounds, including some toxic and persistent substances [70].…”
Section: Composition and Abundance Of Skin Microbiotamentioning
confidence: 99%
“…Lactobacillus agilis [122], Lactobacillus caucasicus [19], Lactobacillus gallinarum [31], Lactobacillus gastricus [90], Lactobacillus johnsonii [24], Lactobacillus kunkeei [123], Lactobacillus murinus [124], Latilactobacillus sakei [102], Lactobacillus vaginalis [106] and Lacticaseibacillus zeae [58] were each only reported once. Among Bacilli, Bacillus subtilis was the most frequently reported species (five times) [125][126][127][128][129], followed by Bacillus velezensis (two times) [130,131]. Bacillus thuringiensis [46], Bacillus amyloliquefaciens [126], Bacillus cereus [132] and Bacillus pumilus [133] were each reported once.…”
Section: Species Reported To Suppress Eskapee Pathogen Growthmentioning
confidence: 99%
“…Six studies were based exclusively on in vivo experiments. These included three rat disease models, two of which were for wounds [53,54] and one was for surgical implants [55], two murine disease models [145], one of which also included a bovine disease model [130], one rabbit model knee implant infection [76] and one bee model [123]. Three studies were based on combined in vitro and in vivo experiments and exclusively included murine disease models, two intestinal colonization models [36,52] and one urinary tract infection model [113].…”
Section: Nature Of Conducted Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A separate study that evaluated S. aureus biofilm formation in vitro reported that DNA of biofilm samples from medical device substrates treated with B. velezensis AP183 prior to subsequent S. aureus colonization revealed a significant relative abundance of B. velezensis, at 96.5% against S. aureus, at 3.5% based on ribotype relative abundance data 29 . The same study showed that B. velezensis AP183 could disrupt formed biofilms of S. aureus and noted the application of beneficial bacterial biofilms, which could hinder the adhesion and biofilm formation of pathogenic bacteria such as S. aureus as a prophylactic advantage.…”
Section: Bacillus Spp Isolates From Soil Inhibit Biofilm Formation Of...mentioning
confidence: 99%